2011
DOI: 10.1038/ncomms1408
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis nitrate reductase activity is stimulated by the E3 SUMO ligase AtSIZ1

Abstract: Small ubiquitin-related modifier (SUMO) is a small polypeptide that modulates protein activity and regulates hormone signalling, abiotic and biotic responses in plants. Here we show that AtSIZ regulates nitrogen assimilation in Arabidopsis through its E3 SUMO ligase function. Dwarf plants of siz1-2 flower early, show abnormal seed development and have high salicylic acid content and enhanced resistance to bacterial pathogens. These mutant phenotypes are reverted to wild-type phenotypes by exogenous ammonium bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
149
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(154 citation statements)
references
References 57 publications
4
149
1
Order By: Relevance
“…It is thus plausible that the lack of efficient nitrate reduction is responsible for the accumulation of nitrate. This interpretation is supported by the finding that siz1 and siz1 pial double and triple mutant combinations grow better in presence of additional ammonium ions (Park et al, 2011; data not shown). We conclude from the data that PIAL1 and PIAL2 have only minor influence on nitrate metabolism.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…It is thus plausible that the lack of efficient nitrate reduction is responsible for the accumulation of nitrate. This interpretation is supported by the finding that siz1 and siz1 pial double and triple mutant combinations grow better in presence of additional ammonium ions (Park et al, 2011; data not shown). We conclude from the data that PIAL1 and PIAL2 have only minor influence on nitrate metabolism.…”
Section: Discussionsupporting
confidence: 77%
“…Measurement of nitrate content further supports this notion ( Figure 6A). Nitrate reductase (NR) is a known substrate of SIZ1-dependent SUMO conjugation and is activated by sumoylation (Park et al, 2011). Increased levels of nitrate in siz1 mutants are consistent with Plants were grown on plates containing 150 mM NaCl as in Figure 2.…”
Section: Assessment Of Metabolite Differencesmentioning
confidence: 63%
See 2 more Smart Citations
“…Although there are several SUMO proteins, only two SUMO E3 ligases have been characterized in Arabidopsis-SIZ1 and MMS21/HPY2 (Huang et al 2009;Ishida et al 2009;Miura et al 2005). The siz1 and mms21/hpy2 mutants exhibit pleiotropic phenotypes that involve ABA (abscisic acid), biotic, and Copyright © 2014 The Japanese Society for Plant Cell and Molecular Biology abiotic stress (heat, cold, salt, and drought) responses, nutrient availability, plant development, and flowering (Catala et al 2007;Chen et al 2011;Jin et al 2008;Lee et al 2007;Miura et al 2007b;Miura et al 2011a;Miura and Ohta 2010;Miura et al 2011b;Park et al 2011;Yoo et al 2006). These findings indicate the importance of SUMO E3 ligases in plants.…”
mentioning
confidence: 99%